THE EFFECT OF ROOTSTOCK AND AGE TREES ON THE GROWTH AND CROPPING OF SZAMPION CULTIVAR APPLE TREES - Magdalena Kapłan; Piotr Baryła (Acta Scientiarum Polonorum: Hortorum Cultus, 2005)
In 2001–2003 on Sandomierska Upland researches were done in order to estimate the influence of the rootstock and the age on the growth and yielding of the ‘Szampion’ trees. This cultivar was grafted on P60 and M.26 rootstock. It was stated that the ‘Szampion’ had given abundant crops (73–113 t/ha on average) due to magnificent conditions of Sandomierska Upland. The height of the yield depended in a significant way on the rootstock (six-year-old trees on P60 yielded considerably better than on M.26) and the age of trees – the trees on M.26 younger by 2 years provided a significantly better yield. The growth and quality of fruits of the ‘Szampion’ depended on the age of scrutinized trees. The proportion of fruit with the diameter of more than 7.0 cm in all the studied combinations exceeded 80% and it was the highest in the trees on P60.